Investigation on the use of tilapia green water and probiotics as an approach to,eliminate vibrio parahaemolyticus and vibrio cholerae in cultured green mussel, perna viridis - Sampollo, Leslie
Vibrio parahaemolyticus and Vibrio cholera are two widely known pathogens that cause human food-borne diseases including gastroenteritis and cholera respectively. Pathogenic Vibrios are also reported to cause mass mortality in aquaculture, even in molluscan bivalves. One of the most affected species is the Perna viridis (green mussel), an important commodity in the Philippines. With this various depuration methods have been constantly investigated in attempts to eliminate the pathogenic vibrio. The most widely used method is the use of UV-light treatment because it does not have harmful residues. However, reports have shown that UV depuration method alone cannot completely eliminate these pathogenic bacteria. Al, Vibrio with the use of Tilapia Green Water and Probiotics. Results have shown that both Tilapia Green water and Probiotics can significantly decrease the levels V. parahemolyticus and V. cholera down to the safe levels. Furthermore, this study suggests that the probiotic Streptococcus spp. is the best alternative method when administered at 109 cfu/ml as it can completely decrease V. parahaemolyticus and V. cholera within 24 hours. Furthermore, the study also proves that Streptococcus spp. does not impose harmful effects to the green mussel as the experimental animal exhibited 100% survival by the end of the depuration process. Overall, this study provides strong evidence that depuration can be effectively done using probiotics.